Entrepreneurship in the raw materials sector: Proceedings of the LIMBRA International Scientific Conference - Zoltán Bartha; Tekla Szép; Katalin Lipták; Dóra Szendi (CRC Press, 2022)
The Entrepreneurship in the Raw Materials Sector proceeding is a collection of papers focusing on the macroeconomic aspects of green growth, the business opportunities in the raw materials sector, and the challenges in entrepreneurship, entrepreneurship training. These papers were presented during the closing conference of LIMBRA (Decreasing the negative outcomes of brain drain in the raw materials sector), a project funded by EIT Raw Materials in the period of 2019-2021. LIMBRA primarily aims at generating new entrepreneurial ideas in the raw materials sector, and to encourage engineering students graduating in raw materials-related programmes to start their own businesses. This proceeding offers a good summary of our approach, and our results: identify the critical trends in the macroeconomic environment; learn about the specifics of the raw materials markets; develop new business ideas, and rely on your local ecosystem for extra knowledge, mentoring; and finally, help students to "Become stay-at-home entrepreneurs."
Keywords: 330; best practice; empirical analysis; raw materials